Physical Education, Sport, and Health Education as Stunting Intervention in Mattirowalie Village - Dos Santos, Maria Herlinda; Rahmat Ilahi; Hezron Alhim Dos Santos; Endang Pratiwi; Sugirah Nour Rachman; Rita Ernita (Universitas PGRI Palembang, 2025)
This research was conducted because of the high rate of stunting in Bone Regency. Bone Regency itself is the area with the most stunting sufferers in South Sulawesi. Stunting is a condition of failure to thrive in five year old children, this occurs due to malnutrition or recurrent infections, especially in the first 1,000 days of life (HPK). The high rate of stunting was also noted by Riskesdas, that there were 9 million children under five experiencing stunting. As a result, many children are shorter in height and tend to be slow in thinking or do not receive optimal cognitive, motor and verbal development. This research was carried out in Mattirowalie, precisely at SMPN 9 Watampone, with the research subjects being 50 class VII students. The method used is class action (which is an examination of learning activities in the form of an action, which is deliberately created and occurs in a class together. This action is given by the teacher or with direction from the teacher which is carried out by students). The research object is Physical Education, Sports and Health. This research stage went through a pre-cycle and two cycles. The first cycle consists of the stages of planning, implementation (action), reflection observation. This research uses a qualitative approach. The results of this research are that in the pre-cycle phase, there was 1 female student who knew for sure, 8 female students who knew partially, 11 female students who were unsure and 30 female students who did not know at all what stunting was. After carrying out the first and second cycles, the results showed that there were 38 female students who knew for sure, 12 female students who knew partially, 0 were unsure and 0 did not know.